Phase transitions in Sn₂P₂S₆ ferroelectric under high pressures - Slivka, A.G.; Gerzanich, E.I.; Guranich, P.P.; Shusta, V.S.; Kedyulich, V.M. (Condensed Matter Physics, 1999)
We have made dilatometric studies of phase transitions in Sn₂P₂S₆ ferroelectric under high hydrostatic pressures. We investigated the pressure
dependence of the coefﬁcients in an expansion of the thermodynamic potential in the order parameter in the vicinity of the Lifshitz point. Проведені дилатометричні дослідження фазових переходів в сегнетоелектриках Sn₂P₂S₆ в умовах високих гідростатичних тисків. Встановлені баричні залежності коефіцієнтів розкладу термодинамічного
потенціалу в ряд за степенями параметра порядку в околі точки Ліфшиця.